2014
DOI: 10.14797/mdcj-10-2-111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dexmedetomidine versus Propofol for Sedation in Mechanically Ventilated Patients after Cardiovascular Surgery

Abstract: Many cardiovascular surgeries are fast-tracked to extubation and require short-term sedation. Dexmedetomidine and propofol have very different mechanisms of action and pharmacokinetic profiles that make them attractive sedative agents in this patient population. Recently, there has been increased use of dexmedetomidine in the intensive care unit (ICU), but few studies exist or have been published directly comparing both agents in this setting. We conducted a retrospective cohort study with patients admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…Recent researches indicate that providing "analgesic priority" treatment program can effectively improve the patient's comfort for the ICU patients [9][10][11][12]. Compared with the traditional sedative treatment, this treatment is beneficial for reducing the patient's stay in the ICU [13]. Therefore, in our study, patients of the two groups were both treated with opioid analgesics and continuous perfused analgesia with hydromorphone, and then, sedation is achieved with midazolam and dexmedetomidine.…”
Section: Discussionmentioning
confidence: 98%
“…Recent researches indicate that providing "analgesic priority" treatment program can effectively improve the patient's comfort for the ICU patients [9][10][11][12]. Compared with the traditional sedative treatment, this treatment is beneficial for reducing the patient's stay in the ICU [13]. Therefore, in our study, patients of the two groups were both treated with opioid analgesics and continuous perfused analgesia with hydromorphone, and then, sedation is achieved with midazolam and dexmedetomidine.…”
Section: Discussionmentioning
confidence: 98%
“…The benefits of propofol include reduced time in the ICU, duration of mechanical ventilation, and incidence of delirium compared with benzodiazepines sedations . Dexmedetomidine was approved in 1999 by the US Food and Drug Administration for sedation in mechanically ventilated patients during the first 24 hours and in nonintubated patients before and/or during surgical or nonsurgical procedures …”
Section: Discussionmentioning
confidence: 99%
“…15,17 Dexmedetomidine was approved in 1999 by the US Food and Drug Administration for sedation in mechanically ventilated patients during the first 24 hours and in nonintubated patients before and/or during surgical or nonsurgical procedures. 18 Although the impact of treatments in the ICU on cognitive functioning is increasingly recognized, 19 relatively few published studies have investigated the impacts of sedation medicine on patients discharged from the ICU. Our research showed for the first time that dexmedetomidine and propofol demonstrated different levels of cognitive intervention on the elderly patients discharged from the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Goals of anesthesia for coronary artery bypass graft (CABG) surgery include hypnosis, hemodynamic stability, neurohumoral stress ablation 4 and may include early tracheal extubation 5 . Fasttrack cardiac surgery is partly dependent on smaller-dose opioid regimens and although these may be associated with increased hemodynamic responses during surgery, there is no apparent increased risk of complications 5 .…”
mentioning
confidence: 99%
“…Fasttrack cardiac surgery is partly dependent on smaller-dose opioid regimens and although these may be associated with increased hemodynamic responses during surgery, there is no apparent increased risk of complications 5 .…”
mentioning
confidence: 99%